Evaluation of Stellar Parameters and Calibrating the Surface Gravity log g for LAMOST-II Median Resolution Survey. (26th March 2021) - Chen, Xiang-Lei; Luo, A-Li; Chen, Jian-Jun; Du, Bing; Wang, Rui; Zuo, Fang; Zhang, Shuo; Li, Yin-Bi; Lu, Yan; Chen, Jing; Qu, Caixia
Abstract: The LAMOST II survey began in the fall of 2018, and LAMOST formally released the obtained medium-resolution spectra (MRS) as well as catalogs of stellar parameters and radial velocities (RV) derived from the MRS in the seventh LAMOST data release (DR7). Compared with the RVs and parameters from high-resolution SDSS14/APOGEE spectra, nearly no RV discrepancy was found, with only dispersion around one km s −1 . The T eff of MRS was 27.79 K systematically lower than that of APOGEE, and the 1 σ difference was approximately 60.40 K. For metallicity, the [Fe/H] of the MRS was 0.11 dex poorer than that of APOGEE, with a dispersion of 0.07 dex. More apparently, the offset of log g was 0.14 dex, and the scatter was 0.23 dex. The gravities of APOGEE have been corrected through seismological data. Similarly, in this study, we tried to calibrate LAMOST MRS log g with the Kepler data for red clump stars and red giant branch stars based on two fitted calibration relations. In addition, we found log g of a small fraction late-K type giants mistakenly measured as dwarfs, and vice versa, on the HR diagram generated with LAMOST T eff and Gaia absolute magnitudes. This was because the MRS parameters were measured from blue band spectra only. The measurements of log g for late-K stars can be significantly improved by adding red spectra.